2020
DOI: 10.3390/jmse8030207
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Whole Thraustochytrid Biomass to Cultured Atlantic Salmon (Salmo salar) Fingerlings: Culture Performance and Fatty Acid Incorporation

Abstract: Replacement of fish oil by 5% thraustochytrid whole cell biomass in diets for Atlantic salmon had no ill effect on fish growth performance, carcass total lipid and total fatty acid content. Carcass fatty acid composition indicated incorporation of the dietary thraustochytrid-derived fatty acids. This was confirmed by compound specific stable isotope analysis (CSIA) which revealed significantly 13C-depleted (δ13C value of −24‰) ω3 long-chain (≥C20) polyunsaturated fatty acids (ω3 LC-PUFAs) in the fingerlings fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…So far, only few studies have reported the effects of whole S. limacinum cell biomass in fish diet on fish growth performance and most of them were focused on Atlantic salmon (Salmo salar) (Carter et al, 2003;Kousoulaki et al, 2015;Katerina et al, 2020;Lee Chang et al, 2020;Hart et al, 2021). In agreement with our data, results from those studies commonly indicated normal fish growth, demonstrating that S. limacinum is a source of highly digestible (98%) PUFAs and proteins for farmed fish.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…So far, only few studies have reported the effects of whole S. limacinum cell biomass in fish diet on fish growth performance and most of them were focused on Atlantic salmon (Salmo salar) (Carter et al, 2003;Kousoulaki et al, 2015;Katerina et al, 2020;Lee Chang et al, 2020;Hart et al, 2021). In agreement with our data, results from those studies commonly indicated normal fish growth, demonstrating that S. limacinum is a source of highly digestible (98%) PUFAs and proteins for farmed fish.…”
Section: Discussionsupporting
confidence: 89%
“…Although several studies have examined the replacement of dietary FO with MO from Schizochytrium spp. in fish and shrimp feeds (Harel et al, 2002;O'Grady and Morgan, 2011;Lung et al, 2016;Katiyar et al, 2017;Allen et al, 2019;Glencross et al, 2020b), only very few studies have reported using the whole of cell biomass of this strain in fish feeds (Kousoulaki et al, 2015;Katerina et al, 2020;Lee Chang et al, 2020;Hart et al, 2021). By using the harvested Schizochytrium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the authors found no impacts on the sensory attributes of the flesh from fish fed the Schizochytrium SCP based on the analysis of a trained sensory panel [115]. In addition to reporting enhanced levels of DHA in the flesh of Atlantic salmon fed a different Schizochytrium SCP, Sprague et al [122] also reported a reduction in the levels of persistent organic pollutants such as polychlorinated biphenyls.…”
Section: Product Quality Influencesmentioning
confidence: 96%
“…Similarly, Chang et al [122] fed whole thraustochytrid (Aurantiochytrium sp. TC20) biomass to S. salar fingerlings to successfully replace the fishoil component in their diets.…”
Section: Salmonidsmentioning
confidence: 99%
“…For example, species of the genera Thraustochytrium , Nannochloropsis , Attheya , Pseudonitzschia , and Rhodomonas possess the ability to produce a number of LC omega-3 containing oils, especially DHA and eicosapentaenoic acid (EPA, 20:5ω3). This has led to a growing interest in the use of marine protist class thraustochytrid-derived oils for human nutrition and aquaculture feed, with nutritional and functional benefits [ 4 , 5 ]. Our previous studies have shown the high triacylglycerol (TAG) content in strain TC 20, containing high proportions of omega-3 LC-PUFA, in particular DHA [ 6 ].…”
Section: Introductionmentioning
confidence: 99%